IMF Staff papers : Volume 29 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1982)
This paper analyzes determinants of the evolution of exchange rates within the context of alternative models of exchange rate dynamics. The overshooting hypothesis is examined in models that emphasize differential speeds of adjustment in asset and goods markets as well as in models that emphasize portfolio balance considerations. It is shown that exchange rate overshooting is not an intrinsic characteristic of the foreign exchange market and that it depends on a set of specific assumptions. It is also shown that the overshooting is not a characteristic of the assumption of perfect foresight, nor does it depend in general on the assumption that goods and asset markets clear at different speeds. If the speeds of adjustment in the various markets are less than infinite, the key factor determining the short-run effects of a monetary expansion is the degree of capital mobility. When capital is highly mobile, the exchange rate overshoots its long-run value, and when capital is relatively immobile, the exchange rate undershoots its long-run value. When internationally traded goods are a better hedge against inflation than nontraded goods, the nominal exchange rate overshoots the domestic price level, and conversely.